Ultrasonic-assisted wetting and soldering of AlN ceramic by using a nonactive solder (Sn9Zn) in air. Issue 2 (15th January 2022) - Chen, Shu; Xu, Zhiwu; Li, Zhengwei; Ma, Zhongwei; Zhang, Mukun; Lu, Yuansong; Yan, Jiuchun
Abstract: AlN ceramic was successfully wetted and then joined with nonactive Sn9Zn eutectic solder assisted by ultrasonication in air. The effect of ultrasonic time on the formation of joint was studied. Results indicated that the defect-free joint can be obtained at an ultrasonic time of 5 s. Two regions, namely, AlN/Sn (s, _s) and AlN/Zn (s, _s), were found in the bonding interface. Zn and O accumulated in the AlN/Sn (s, _s) interface. An amorphous and nanocrystalline layer of ZnO formed in the hard-wet AlN surface. And Zn (s, _s) directly bonded with AlN. The low temperature and fast bonding of the AlN was attributed to the high pressure and temperature caused by cavitation effect. The shear strength of the joint increased from 10.6 MPa to 30.7 MPa when the ultrasonic treatment time increased from 5 s to 150 s. With the prolongation of ultrasonic time, more AlN ceramic particles entered the solder and acted as the reinforcing phase. Highlights: AlN ceramic was rapidly wetted with a nonactive solder (Sn9Zn) in 5 s assisted by ultrasonication at 230 °C. Wetting was realized by an amorphous and nanocrystalline ZnO at AlN/Sn interface, and Zn directly bonded with AlN. The shear strength of the joint was 30.7 MPa with a short wetting time of 150 s. The triggering mechanism of acoustic cavitation on wetting was analyzed through finite element simulation and calculation.